PENGARUH DAN DAMPAK PEMBAHARUAN HUKUM ISLAM TERHADAP KEWARISAN BEDA AGAMA (Study Komparatif Pemikiran Wahbah Az Zuhali dan Yusuf Al-Qaradhawi) - Anwar Hafidzi; Ajeng Juniwanti; Lailan Mufthirah; Rina Mahdiana (STAI AL FALAH Banjarbaru, 2019)
In Islamic law, there are some reasons so that one can receive the inheritance of which is because of the Nasabiyah, marriage, and Wala al Itqi. But there are some exceptions to religious differences. The scholars differed about the ability or absence of a Muslim inheriting from nonmuslims and vice versa. The main focus of this research is the thought of the Wahbah Zuhaili and Yusuf Al-Qardawi as contemporary scholars. The method used in this study is the research method of Library Research, the method of approach used in this research is the approach of analytical approach (analytical approach) and historical Approach. The results obtained are analyzed to find how the scholars, in this case, are the Wahbah Zuhaili and Yusuf Al-Qardawi in interpreting the Nash and bring about the renewal of the law against religious inheritance issues as an obstacle to Inherited between Muslims and Nonmuslims. Keywords: renewal, law, inheritance, religious differences.